GENUS LYCIUM MILL. OF THE FAMILY SOLANACEAE: BOTANICAL CHARACTERISTICS, BIOLOGICAL FEATURES AND PROSPECTS FOR UTILIZATION - Nurmamatova Feruza Mukhtor kizi, Siddikova Shakhnoza Akhmedovna (Ethiopian International Journal of Multidisciplinary Research, 2026)
This article presents a scientific review of the genus Lycium Mill., belonging to the family Solanaceae. The taxonomic position, morphological structure, ecological adaptability, geographical distribution, biochemical composition, and practical significance of representatives of this genus are analyzed. Particular attention is paid to medicinal properties, biologically active compounds, and prospects for introduction and cultivation in arid regions. It has been established that species of the genus Lycium are of considerable interest for pharmacology, food production, agriculture, and environmental restoration.